ANALISA PERTANGGUNGJAWABAN PIDANA KORPORASI TINDAK PIDANA PERDAGANGAN ORANG (PUTUSAN NOMOR 112/Pid.Sus/2015/PN.Tul) - Aris Pebriwadi Sinaga,; Danu Setiawan Eko Wardana,; Parningotan Malau, (Journal of Innovation Research and Knowledge, 2026)
Human trafficking is a crime involving enslavement through recruitment by means of sending, harboring, and the use of threats, violence, and confinement. This study will analyze the process of criminal liability for human trafficking committed by corporations. The research method used is normative legal research. It uses literature review and case study methods from Supreme Court Decision Number 112/Pid.Sus/2015/PN.Tul. The results of the research on corporate involvement represent criminal liability using the Vicarious Liability Theory.